PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KINERJA KARYAWAN PADA PT ISS INDONESIA AREA GELORA BUNG KARNO - Lauren Santosa, Melinda Angelina; Andi, Dede (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine To determine the effect of motivation on employee performance of PT ISS Indonesia GBK Area partially To determine the effect of discipline on employee performance of PT ISS Indonesia GBK Area partially To determine the effect of motivation and discipline on employee performance of PT ISS Indonesia GBK Area simultaneously. The sample used was the slovin sample technique which amounted to 112 employees. Data collection techniques through primary and secondary data. The method used is quantitative with an associative approach. The results showed that: (1) partially that motivation has a positive influence on employee performance this can be proven from the linear regression test has a regression equation value Y = 2.664 + 0.087 X1, it can be concluded that the constant value is 2.664. Hypothesis testing found that the tcount is greater than the ttable (8.815 greater than 1.982) with a significant level of 0.000 <0.05 (2) partially that discipline has a positive influence on employee performance this can be proven from the results of the linear regression test has a regression equation value Y = 2.730 + 0.831 X2, it can be concluded that the constant value is 2.730. Hypothesis testing found that tcount is greater than ttable (17.774> 1.982) with a significant level of 0.000 <0.05. Therefore, it can be said that work discipline has a positive and significant effect on employee performance. (3) simultaneously the effect of motivation (X1) and discipline (X2) on employee performance.